An integrative neurogenomics workflow for precision medicine in neurodegenerative disorders - Perezcano, Carlos; Pérez-Coria, Mariana (Frontiers in Dementia, 2026)
Neurodegenerative diseases represent an expanding global health challenge, with rapidly increasing prevalence and substantial economic impact. The therapeutic clinical approach continues to seek solutions through pharmacological means—such as inhibitors and antibodies—which, while sometimes controlling symptoms, have not addressed the underlying pathophysiology. By integrating advanced genomics with selected biochemical markers, under the continuous oversight of a multidisciplinary team working in consensus, it is possible to achieve a more comprehensive understanding of individual phenotypes, enabling the design of truly personalized neurogenomics-based functional plans. This article outlines the steps of the proposed integrative neurogenomics workflow, discussing its advantages and limitations, and presents highlights from an illustrative case intended as a potential reference model to establish the foundation for a new standard of personalized genomic medicine in neurodegeneration. The workflow underscores the importance of considering the additive burden of genetic variants typically classified as benign—beyond the ACMG pathogenicity framework—for accurate phenotypic assessment. It further demonstrates the feasibility of developing actionable and highly precise functional interventions by integrating genomic and biochemical data. Findings from the case example reveal correlations between genetic variants and biochemical markers, providing the basis for personalized recommendations in nutrition, lifestyle, and supplementation. This framework aims to establish the foundations of personalized genomic medicine in neurodegenerative diseases, underscoring the urgent need to move beyond one-size-fits-all approaches.